The Effect Of Face Print Attendance On Employee Performance With Supervision As A Moderation Variable At The Samosir Regency Food Security And Agriculture Office - Marganda P. Sitanggang; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2025)
The purpose of this study is to find out and analyze the effect of Face Print Attendance on Employee Performance mediated by Supervision on Employees of the Samosir Regency Food Security and Agriculture Office. This research was carried out at the Samosir Regency Food Security and Agriculture Office. The type of research is quantitative associative. The sample in this study is 64 employees of the Samosir Regency Food Security and Agriculture Office. The sampling technique in this study uses a saturated sample so that the entire population will be a sample of 64 people. The results showed that Face Print Attendance had a significant effect on Employee Performance (T-Statistic = 5,702, P-Value = 0.000) and on Supervision (T-Statistic = 4,152, P-Value = 0.000). Supervision also has a significant influence on Employee Performance (T-Statistic = 22,736, P-Value = 0.000). However, as a moderation variable, Supervision does not strengthen the relationship between Face Print Attendance and Employee Performance. In other words, an increase in Face Print Attendance can directly improve Employee Performance, but not through an increase in Supervision. This shows that the improvement in Face Print Attendance does not have an impact on Supervision, so it does not contribute further to improving the Performance of Employees of the Samosir Regency Food Security and Agriculture Service